Relationship Between Environmental Sanitation And Flies Density Levels In The Inpres Market Bangkinang City - Sofi Asri Rahayu; Dessyka Febria; Ade Dita Puteri (Excellent Health Journal, 2025)
According to the World Health Organization (WHO), more than 700,000 deaths are recorded every year worldwide, some of which are transmitted via fly vectors, which cause 17% of all infectious diseases. The aim of this research is to determine the relationship between environmental sanitation and the level of fly density at the Bangkinang City Presidential Market in 2023. This research is an observational research, with a cross sectional approach, the research was conducted on 25-30 November 2023. The population in this research was 58 chicken, fish and meat traders. The sampling technique was carried out by total sampling. The measuring tool used is an observation sheet and the fly density measuring tool is a flygrill. The analysis used is univariate and bivariate, processed using a computerized system. The data obtained were analyzed using the Chi-Square test. The results of the research show that there is a relationship between environmental sanitation p value = 0.002 and the level of fly density at Bangkinang Inpres Market. This research hopes that traders will pay more attention to the condition of the rubbish that is still lying around, especially vegetable traders, to throw rubbish in the right place so as not to cause flies to breed.